Factors that influence the inclusion and participation of disabled students in higher education - Abrahams, Dureyah (Division of Disability Studies, 2024)
This document summaries and synthesises the results of an investigation aimed to explore factors that influence disabled students' inclusion and participation in higher education in the Western Cape. Disabled students face many challenges in education in South Africa due to inadequate accessibility and inclusion. There is minimal research of disabled students' experiences in South Africa who succeed in entering a university, and the voices of disabled South African students are underrepresented. The aim of this study is to explore the factors that influence disabled students' inclusion and participation in higher education. The objectives of this study are to: ● Explore how products and technology influence participation and inclusion ● Explore how the natural environment influences inclusion and participation ● Understand how the nature of support and relationships and attitudes of different role players influence inclusion and participation ● Determine how services, systems and policies influence inclusion and participation ● Suggest what changes need to be implemented to improve inclusion and participation This study used a qualitative single-case study research design, with an emancipatory disability research lens. Data was gathered through four focus groups with a total of ten disabled students at the University of Cape Town (UCT), in the Western Cape of South Africa. The participants identified with varying disabilities, genders, age, course enrolment and races. The findings that emerged relate to two themes. Theme 1, “Accessibility equals success”, uncovers three sub-themes “availability of resources”, “make it feel as inclusive as possible”, and “dualities of remote learning”, which highlight disabled students' needs for assistive technology and financial support, the inaccessible physical spaces and facilities, and the experiences of remote learning in the COVID-19 pandemic. Theme 2, “fostering inclusion”, focussed on four sub-themes, “supporting well-being”, “Disability Services played a vital role”, “I am asking for accommodation”, and “being there emotionally”. These sub-themes highlight the support systems that disabled students valued, such as the Disability Services of the Office of Inclusivity and Change (OIC), the Student Wellness services, peer and family support. There remains to be a general experience of exclusion in spaces and systems at UCT, as disabled students detail experiences of isolation, stigma, stress and othering. Similarly, social exclusion to the spaces, xii resources and culture of university life is a common experience. This social exclusion is noted as contributing to disabled students' declining mental health, quality of life and low feelings of belonging. This study argues that disabled students require a holistic approach to inclusion, where academic, physical and social inclusive practices and services are improved. Further to this, there is a need for anchoring disability transformation in the UCT Vision 2030, with the inclusion of the voices and experiences of disabled students.